Nanowires: Large‐Scale Assembly of Single Nanowires through Capillary‐Assisted Dielectrophoresis (Adv. Mater. 7/2015). (February 2015) - Collet, Maéva; Salomon, Sven; Klein, Naiara Yohanna; Seichepine, Florent; Vieu, Christophe; Nicu, Liviu; Larrieu, Guilhem
<x xml:space="preserve">Abstract</x> G. Larrieu and co‐workers demonstrate on page 1268 an innovative approach that combines the dielectrophoresis phenomenon and capillary assembly for the precise and scalable placement of thousands of single nanowires. The nanowires are selectively trapped by taking advantage of the material‐specific frequency dependence, which allows, for example, NW sorting, starting from a solution containing a mixture of several kinds of NWs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>